Pengaruh Pengembangan Karir Dan Komitmen Organisasi Terhadap Kinerja Karyawan Pada PT. Gaya Makmur Tractors Makassar - Reski Bubung; Rina Rina; Kamaruddin Kamaruddin (Master Manajemen, 2023)
The purpose of this study is to understand how career development and organizational commitment affect how employee performance at PT. Gaya Makmur Tractors Makassar. This data is surveyed to obtain primary data. The slovin formula was used in the study, and a total of 90 people were sampled. The validity and reliability of these findings have been evaluated, through heteroscedasticity, multicollinearity, and normality tests have all been considered. The data analysis method uses multiple regression.